2015
DOI: 10.1002/2015pa002830
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for the influence of ice‐rafted detritus on grain size‐based paleocurrent speed estimates

Abstract: The grain size of deep-sea sediments provides an apparently simple proxy for current speed.However, grain size-based proxies may be ambiguous when the size distribution reflects a combination of processes, with current sorting only one of them. In particular, such sediment mixing hinders reconstruction of deep circulation changes associated with ice-rafting events in the glacial North Atlantic because variable ice-rafted detritus (IRD) input may falsely suggest current speed changes. Inverse modeling has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Current-sorting of marine muds has only been sparsely investigated in glaciomarine environments 37 as the deposition of large ice-rafted clasts can potentially interfere with the current-sorting signal by shielding underlying sediment from winnowing 38 41 . However, deposition of ice-rafted debris is only problematic when sedimentation rates are rapid (>1 cm yr −1 ); in areas with lower sedimentation rates well-sorted sediments can be produced under just a few days of fast-flow conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Current-sorting of marine muds has only been sparsely investigated in glaciomarine environments 37 as the deposition of large ice-rafted clasts can potentially interfere with the current-sorting signal by shielding underlying sediment from winnowing 38 41 . However, deposition of ice-rafted debris is only problematic when sedimentation rates are rapid (>1 cm yr −1 ); in areas with lower sedimentation rates well-sorted sediments can be produced under just a few days of fast-flow conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Smear slide examination showed negligible amounts of biogenic carbonate and opaline silica, suggesting an insignificant or negligible influence of these particles to the estimate of the S̅S̅ record of core Hu06‐40. Hass [] demonstrated that in some circumstances the contribution of ice‐rafted detritus (IRD) led to variation in the S̅S̅ [ Jonkers et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean size of the sortable silt (S̅ S̅ ) in core Hu06-40 is hypothesized as a proxy for the Labrador Current speed. Silt fractions (63-10 μm) of the terrigenous sediments can be sorted by the prevailing bottom currents of the ocean on the basis that these fractions are noncohesive and are therefore sorted by Hass [2002] demonstrated that in some circumstances the contribution of icerafted detritus (IRD) led to variation in the S̅ S̅ [Jonkers et al, 2015].…”
Section: Mean Sortable Silt Size As a Proxy For The Labrador Currentmentioning
confidence: 99%
“…As an example, we tested the method on a sediment core containing variable amounts ice-rafted debris (IRD), that is, sediments transported by ice rafting (Almirantazgo fjord, Chile, 54°S; Figures S3 and S4; Bertrand et al, 2017). Ice rafting deposition results in the presence of large particles in the sediment and skews the entire grain-size distributions toward the coarse fraction (Hass, 2002;Jonkers et al, 2015), without necessarily significantly changing sediment geochemistry. In this case, the prediction accuracy decreases with increasing amounts of IRD ( Figure S4).…”
Section: Potential and Restrictions Of The Methodsmentioning
confidence: 99%